Implementación de una planta piloto para la elaboración de cerveza artesanal, en el complejo agroindustrial de la Universidad Estatal de Bolívar - Guambuguete Yauqui, Gladys Rocío (2025)
The objective of the research was to implement a pilot plant for the production of craft beer at the Bolívar State University's Agroindustrial Complex. A study was conducted to determine a suitable and safe location for its installation. For this process, the production of pale ale craft beer was determined. The brewing equipment's respective operation was demonstrated, as well as the 80% efficiency of the equipment for the production of fermented products within the agroindustrial plant. To produce this product, the raw material, barley obtained from the city of Guaranda, was received. This process allowed the determination of the different times and temperatures during its production, achieving a 5% alcohol content in the brewed beer. In addition, a mass balance was determined for each stage during its production, where the percentage of material entering and exiting could be evidenced, taking into account the losses during its process such as cooking and fermentation, the sedimentation of the wort, thus obtaining a production of 32.2 liters of brewed beer.